Artificial Intelligence in Predictive Policing: A Systematic Literature Review and Its Implications for Indonesia - Wibisono, Radyan Kunto; Joko Setiono; Prisgunanto, Ilham (Greenation Publisher & Yayasan Global Resarch National, 2025)
The use of Artificial Intelligence (AI) in predictive policing is rapidly developing globally as a response to demands for effectiveness and efficiency in law enforcement. Although this technology promises predictive capabilities that can assist the police in identifying potential crimes in the future, its implementation raises complex legal and ethical issues, especially in the context of a rule-of-law country like Indonesia. This article presents a systematic review of academic literature related to AI in predictive policing over recent years sourced from Scopus, Web of Science, and Google Scholar. The study results indicate that although predictive policing has the potential to reduce crime rates, this technology is fraught with risks of algorithmic discrimination, data bias, privacy violations, and unclear legal accountability. A juridical analysis of existing regulations in Indonesia, such as Law No. 27 of 2022 on Personal Data Protection and the Electronic Information and Transactions Law (UU ITE), shows the absence of legal norms that specifically regulate the application of AI in the context of criminal law. Furthermore, the use of algorithmic prediction results as a basis for legal action potentially contradicts fundamental principles in criminal procedural law, such as the presumption of innocence and the right to personal data protection. This study recommends the urgency of establishing a national legal framework capable of ensuring the ethical, fair, and accountable application of AI technology in law enforcement sectors. Adaptive and human rights-based regulations are necessary so that AI can be used responsibly without sacrificing the values of justice and democracy.